Accuracy of different triage strategies for human papillomavirus positivity in an Italian screening population. Issue 6 (5th November 2021) - Gustinucci, Daniela; Benevolo, Maria; Cesarini, Elena; Mancuso, Pamela; Passamonti, Basilio; Giaimo, Maria Donata; Corvetti, Rosa; Nofrini, Valeria; Bulletti, Simonetta; Malaspina, Morena; Tintori, Beatrice; Giorgi Rossi, Paolo; et al.
Abstract: How to manage human papillomavirus (HPV)‐positive women in cervical cancer screening remains debated. Our study compared different strategies to triage HPV positivity in a large cohort of women participating in a population HPV‐based screening program. Women were tested for HPV (Cobas 4800; Roche), and those positive were triaged with cytology; cytology‐positives were referred to colposcopy, while negatives were referred to 1‐year HPV retesting. All HPV‐positive women were also evaluated with p16/ki67 dual staining (Roche). All lesions found within 24 months of follow‐up were included in the analyses. Of the 70 146 women tested, 4757 (6.8%) were HPV‐positive. Of these, 1090 were cytology‐positive and were referred to colposcopy. Of the 2958 HPV‐positive/cytology‐negative women who presented at 1‐year retesting, 1752 (59.9%) still tested positive. Cumulatively, 532 CIN2+ (including 294 CIN3+) were found. The sensitivity of cytology, HPV16/18 and p16/ki67 as triage test for CIN3+ was 67.9%, 56.0% and 85.0%, respectively. The positive predictive value (PPV) for immediate colposcopy referral was 21.0%, 15.8% and 22.9%, respectively. Combining cytology with typing increased sensitivity to 83.9% and lowered PPV to 14.8%, while combining p16/ki67 and typing increased sensitivity to 91.1%, lowering the PPV to 15.9%. Women negative to p16/ki67 triage presented a cumulative 1‐year CIN3+ risk of about 1%. In conclusion, when triaging HPV positivity, p16/ki67 performed better than cytology with or without HPV16/18 genotyping. The strategies that included dual staining achieved sensitivity and low 1‐year risk for CIN3+ sufficiently high enough to permit considering extending the surveillance interval to 2 to 3 years for HPV‐positive/triage‐negative women. Abstract : What's new? How to manage human papillomavirus (HPV)‐positive women in cervical cancer screening is still debated. In this large population‐based study, the authors evaluated the accuracy and performance of p16/ki67 dual staining, alone or in combination with HPV16/18 typing, as a triage test for HPV‐positive women in comparison with cytology. With or without HPV16/18 genotyping, p16/ki67 performed better than cytology in terms of both sensitivity and positive predictive value for CIN3+. The strategies that included dual staining achieved a high enough sensitivity with a low 1‐year risk of CIN3+ to potentially extend the current surveillance interval for HPV‐positive/triage‐negative women.